SOCIOLOGICAL STUDY ON SEXUALITY IN YOUR NAME ENGRAVED HEREIN BY KUANG-HUI LIU - Ramlan, Mirnadevi; Halim, Abdul (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
The movie "Your Name Engraved Herein," by Kuang-Hui Liu, is the subject of this study. The main character in the movie is homosexual, and the writer aims to explore homosexuality through character. This study applied Alan Swingewood's sociological literature theory, which sees literary works as direct reflections of society. In other words, literary works cannot be separated from the social realities that exist in society. This study aims to find out (1) conflict that experienced by main character as gay (2) the way taken by them to overcome the conflict, and (3) the perception of Taiwanese society towards homosexuals reflected in the movie. The results of this research indicate a correlation between real-life conditions in Taiwan in 1987 and the situation depicted in the movie. In the movie, homosexuality is viewed as a mental illness and disorder. Society believes that keeping gays around them will have a negative impact and may lead to others become same-sex lovers. This state is reflected in Kuang-Hui Liu's and his lover's fear of public judgment.